2012
DOI: 10.5194/acp-12-3659-2012
|View full text |Cite
|
Sign up to set email alerts
|

The 2009–2010 Arctic stratospheric winter – general evolution, mountain waves and predictability of an operational weather forecast model

Abstract: The relatively warm 2009–2010 Arctic winter was an exceptional one as the North Atlantic Oscillation index attained persistent extreme negative values. Here, selected aspects of the Arctic stratosphere during this winter inspired by the analysis of the international field experiment RECONCILE are presented. First of all, and as a kind of reference, the evolution of the polar vortex in its different phases is documented. Special emphasis is put on explaining the formation of the exceptionally cold vortex in mid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
116
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(128 citation statements)
references
References 30 publications
12
116
0
Order By: Relevance
“…In both cases, a reversal of the mean zonal flow direction is measured between 50-55 • N, accompanied by a steep increase of the temperature in the Arctic (blue dashed line). The temperature data are daily and zonally averaged AURA/MLS observations Limpasuvan et al, 2005) between 60-80 • N. The wind and temperature observations are consistent with the analysis of meteorological data in the Arctic of various winters (Labitzke and Kunze, 2009;Manney et al, 2009;Dörnbrack et al, 2012). In the beginning of January, when the vortex had the strongest intensity, the mean eastward zonal-winds strongly increased to 60-80 m s −1 .…”
Section: The Sudden Stratospheric Warming Eventssupporting
confidence: 48%
See 1 more Smart Citation
“…In both cases, a reversal of the mean zonal flow direction is measured between 50-55 • N, accompanied by a steep increase of the temperature in the Arctic (blue dashed line). The temperature data are daily and zonally averaged AURA/MLS observations Limpasuvan et al, 2005) between 60-80 • N. The wind and temperature observations are consistent with the analysis of meteorological data in the Arctic of various winters (Labitzke and Kunze, 2009;Manney et al, 2009;Dörnbrack et al, 2012). In the beginning of January, when the vortex had the strongest intensity, the mean eastward zonal-winds strongly increased to 60-80 m s −1 .…”
Section: The Sudden Stratospheric Warming Eventssupporting
confidence: 48%
“…in December and January) revealing the edge of the Arctic polar Vortex. The dynamics of the Arctic winter 2009/2010 have been described in several studies (Wang and Chen, 2010;Dörnbrack et al, 2012;Kuttippurath and Nikulin, 2012). In early winter, planetary wave activity prevented the formation of a strong vortex in the lower stratosphere and the vortex eventually split at the beginning of December (minor stratospheric warming).…”
Section: Monthly Variation Of Zonal-windsmentioning
confidence: 99%
“…The prevailing cold temperatures in the stratosphere led to considerable denitrification and the strongest depletion of ozone measured in the Arctic . The Arctic winter 2009/2010, on the other hand, was rather warm in the climatological sense but was distinguished by an exceptionally cold stratosphere from mid-December 2009 to mid-January 2010 that led to prolonged PSC formation and significant denitrification (Dörnbrack et al, 2012;.…”
Section: Arctic Winter 2009/2010 and 2010/2011mentioning
confidence: 99%
“…Additionally, during mid-January orographic gravity waves were frequently excited by the flow over Greenland. A major warming in the second half of January (around 24 January) caused a displacement of the vortex to the European Arctic and also initiated the break-up of the vortex Dörnbrack et al, 2012).…”
Section: Arctic Winter 2009/2010mentioning
confidence: 99%
“…Dörnbrack et al, 2012). Figure 1 indicates the minimum temperature (T min ) as a function of day of the year (DOY) derived from the European Centre for Medium-range Weather Forecasts (ECMWF) operational forecasts on the 500 K potential temperature (PT) surface at equivalent latitudes (EQL) greater than 70 • N. The T min for the winter period of 2009/2010 was lower than 185 K from 1 January and became as low as 180 K on 7 January (see also Dörnbrack et al, 2012). Khosrawi et al (2011) reported that strong denitrification caused by the formation of PSCs was observed during the synoptic cooling event in mid-January 2010.…”
Section: Introductionmentioning
confidence: 99%